Applying Butler's Third-Wave Feminist Theory to Environmental Injustice: Innovation in Understanding Gender Performativity in Contemporary Climate Activism (International Journal of Economics Management and Social Science, 2026)
This article examines the application of Judith Butler's third-wave feminist theory, particularly her concept of gender performativity, to contemporary climate activism and environmental injustice. As climate change disproportionately affects marginalized communities, understanding the gendered dimensions of environmental activism becomes crucial for developing inclusive and effective climate action strategies. This study employs a critical theoretical analysis to explore how Butler's performativity framework illuminates the intersection of gender identity, environmental advocacy, and social justice movements. Drawing on contemporary examples of climate activism from various global contexts, we demonstrate how gender is performed, negotiated, and reconstructed within environmental justice movements. Our analysis reveals that climate activism serves as a critical site where traditional gender binaries are challenged, and new forms of gendered political engagement emerge. The findings suggest that integrating Butler's theoretical lens into environmental discourse enables a more nuanced understanding of how power, identity, and ecological concerns intersect. This research contributes to both feminist theory and environmental studies by offering an innovative framework for analyzing the performative aspects of gender in climate activism, ultimately arguing that recognizing these dynamics is essential for building more inclusive and effective environmental justice movements. Keywords: gender performativity, third-wave feminism, Judith Butler, climate activism, environmental justice, intersectionality